Subsurface and bulk mechanical properties of polyurethane nanocomposite films - Kamal Yusoh (2010)
A series of exfoliated and intercalated polyurethane (PU) organoclay nanocomposites, polyurethane-graphite oxide (GO) and polyurethane carbon nanotubes (single-walled (SWNT) and multi-walled carbon nanotubes (MWNT)) were prepared by in situ polymerization. It is believed that the preparation of polymer/clay or polymer/CNTs nanocomposites with homogeneous dispersion of nanofillers in the matrices is a crucial step to developing high-performance polymer nanocomposites. The effects of various organoclays and carbon nanotubes (CNTs), polyol types and dispersion situation i.e. intercalation or exfoliation on viscosity were investigated. The interactions between the polyol and nanofillers and the mixing temperature play an important role in the occurrence of exfoliation and intercalation in polyurethane nanocomposite. The mechanism of exfoliation of clay was proposed based on the rheological data. The surface mechanical properties of the polyurethane nanocomposite films were investigated by means of nanoindentation. The results showed that the hardness and elastic modulus of the nanocomposites dramatically increased with the incorporation of nanofillers. This improvement was dependent on the content of nanofillers as well as the formation structure of organoclay in the polyurethane matrix. At 3wt% clay content, the hardness and elastic modulus of intercalated nanocomposites increased by approximately 16% and 44%, respectively, compared to the pure PU. For the exfoliated clay/PU nanocomposites, the improvement in these properties was about 3.5 (hardness) and 1.6 (modulus) times higher than the intercalated ones. For the polyurethane graphite oxide (GO) nanocomposites both the hardness and the elastic modulus were enhanced as a function of GO concentration. With incorporation of 4wt% GO, the hardness and modulus increased nearly ~400% and ~350%, respectively. Upon incorporation of only 1wt% SWNT, the hardness of polyurethane was greatly improved by about 150% from 3 MPa to 7.8 MPa and the modulus was improved by about 50% from 12MPa to 18.5 MPa. For only 1wt% MWNT, the hardness of polyurethane was improved by about 50% and the modulus is just slightly improved by about ~5%. The creep behaviour of bulk and sub-surface of the polyurethane nanocomposites were investigated by means of uniaxial conventional creep testing and nanoindentation, respectively. The results showed that the creep resistance of the PU was significantly improved by incorporation of nanofillers. The enhancement of creep resistance was dependent on the filler. With 1wt% clay, the creep resistance increased by approximately 50% for the intercalated system and 67% for the exfoliated system, respectively, compared to the pure PU. The elastic-viscoelastic (EVE) model was employed to examine the effect of organoclay loadings on the creep performance of PU nanocomposites. Results showed the model was in good agreement with the experimental data. A similar results were also noticed in polyurethane with GO and CNTs. The creep deformation decreases when the GO content increases, as expected from the addition of a rigid reinforcement of GO and CNTs into a polyurethane matrix. In scratch test, the results pronounced that with incorporation of nanofillers the scratch depth of polyurethane matrix was dramatically reduced.